Correlations between wear mechanisms and rail grinding operations in a commercial railroad. (February 2015) - Cuervo, P.A.; Santa, J.F.; Toro, A.
Abstract: Rail grinding is a typical maintenance procedure for railways in which an abrasive wheel is used to restore the rail profile while eliminating defects such as corrugation, fatigue cracks and detachment marks. In this work, the grinding procedures performed during 10 years in 22 curves of a commercial railway ( Metro de Medellin railway, line B) were studied and classified to understand the most important causes of damage. Periodical inspections were done to identify the main wear mechanisms in the field and the defects were classified into corrugation, fatigue and loss of profile. The results showed that corrugation took place preferentially on the low rail while fatigue was observed preferentially in the high rail. Highlights: Corrugation was located preferentially on the low rail. The most important defects found in rails are head checks. Grinding intervals the 0 to 200 days revealed that 70% are HRC rail profiles. Grinding intervals can be correlated with contact profile, radius and superelevation.